Security Intelligence and Left Intellectuals: Australia, 1970 - Cahill, Rowan (International Gramsci Journal, 2023)
In 1970 the Australian Security Intelligence Organisation (ASIO) identified the ideas of Antonio Gramsci as one of the root causes of dissent, opposition and cultural ferment. This document is an example of ASIO’s concern about Marxist intellectuals and their Gramscian links.